Columnar Phases from Covalent and Hydrogen-Bonded Liquid-Crystalline Ferrocene Derivatives - Deschenaux, Robert; Monnet, Florence; Serrano, Elisabeth; Turpin, François; Levelut, Anne-Marie (My University, 1998)
The synthesis and liquid-crystalline properties of tetracatenar covalent and H-bonded bis-ferrocene derivatives 1 and 2, respectively, are reported. Both compounds gave rise to enantiotropic columnar liquid-crystalline behavior with a hexagonal molecular organization. To explore the possibility to obtain also calamitic liquid-crystalline phases from H-bonded ferrocene-containing liquid crystals, a rod-shaped ferrocene mesogen 3 was synthesized, which gave rise to enantiotropic smectic C and smectic A phases. For the first time, a rational synthetic design at the ferrocene level led to ferrocene-based liquid-crystals with columnar behavior and to H-bonded metallomesogens.
Keywords: ferrocene; fullerene; supramolecular organization